MODEL OF ESTIMATION OF SPECTRAL DENSITY OF POWER OF RISK SIGNALS OF MARINE NAVIGATION EQUIPMENT - Штрибець, В. В.; Василенко, В. М.; Вечурко, О. М. (Science-based technologies, 2019)
It is shown that the purpose of maritime navigation devices is to provide reliable control over the current values of parameters that characterize the modes of the route of the water transport vehicle. The route of the vehicle in difficult meteorological conditions and in the night impossible without equipment, which determine and provide information to the navigator on the position of the means of inland transport in the route relative to the horizon, the direction of its movement, etc. At the spot displays of marine navigational devices, its safe operation is ensured by the safety of naval navigation. The main navigational devices and their purpose are shown. It is substantiated that in the study and measurement of the characteristics of random processes, two classical approaches are used: spectral and temporal. The advantages and disadvantages of these approaches are defined. It is noted that determination of the local estimation of the spectral density of the power of random variables in marine navigational devices is not used due to the complicated technical implementation of known calculation methods. In the known sea navigation devices an integral estimate of the spectral density of the power of random variables is determined. In the research the model of the estimation of the spectral density of the power of the random signals of marine navigational devices, optimized for the possibility of technical implementation and the required accuracy of the determination of navigational parameters during the movement of the vessel, was developed. The proposed model of the estimation of the spectral density of the power of the random signals of marine navigational devices allows to take into account the level of interference that is introduced in the definition of navigation parameters of the vessel during the movement. The use of automatic filters will increase the accuracy of obtaining navigational parameters by the ship's control system during movement. This will increase the safety of the movement and allow you to move along the optimal route according to the established course.